O conhecimento do professor da educação infantil para o ensino de matemática: análise dos livros do PNLD 2019 - Silveira, Ana Paula Bolsan Sagrilo (2023)
In the search for different perspectives to enable support for the training of teachers in the first stage of Basic Education, since 2019 the Brazilian Federal Government has made available the Book of the Teacher of Early Childhood Education, based on the National Book and Teaching Material Program (PNLD), with the purpose of assisting teachers in the development of educational activities. At this context, the researchers aroused the desire to carry out an investigation in these books, focusing on the Mathematics area, specifically the training of Early Childhood Education teachers for the referred area of knowledge. Therefore, it was outlined, as a general objective, to identify which knowledge belonging to the Mathematics Teacher’s Specialized Knowledge (MTSK) can be mobilized in teachers when they read the guidelines and/or develop the pedagogical practices suggested in the Books of the Teacher of Early Childhood Education of PNLD 2019. It used the Mathematics Teachers' Specialised Knowledge (MTSK) model purposed by Carrillo-Yañez, Climent, Contreras e Muñoz-Catalán, as theoretical support. The research was carried out from a qualitative approach, from Gil, and the constructivist paradigm, introduced by Roratto, having been organized in the format of a documental study based on Lüdke and André, which was used to carry out the analysis textual and made it possible to investigate the materials with greater complexity and understanding. The following books constitute the corpus of the research: Aprender com a criança: experiência e conhecimento; Pé de brincadeira: Pré-escola 4 a 5 anos e 11 meses; Práticas comentadas para inspirar: formação de Professores da Educação Infantil e Cadê? Achou! Educar, cuidar e brincar na ação pedagógica da Creche. Based on the analyzed data, it was possible to reach some conclusions, among them, that Early Childhood teachers can mobilize some knowledge from the MTSK knowledge set, such as the Subdomain Knowledge of Topics (KoT) and the categories Phenomenology, Records of Representation and Definitions of Mathematical Themes; the Knowledge Structure of Mathematics (KSM) subdomain and the Cross-Content Connections category; the subdomain Knowledge of Features of Learning Mathematics (KFLM) and the categories Strengths or Difficulties, Ways of Interaction of Students with the Content and Ways of Learning; the subdomain Knowledge of Mathematics Teaching (KMT) and the categories Personal or Institutionalized Teaching Theory, Material and Virtual Resources Associated with Mathematical Content and Tasks, Example, Techniques and Strategies; and, finally, the subdomain Knowledge of Mathematics Learning Standards (KMLS) and the category Mathematical Contents. It was verified that the knowledge of the Mathematical Knowledge (MK) domain is less explored in books than knowledge in the Pedagogical Content Knowledge (PCK) domain. However, although the PCK categories and subdomains prevail in the works, it is still insufficient, as several of its knowledge are not contemplated. It is noted, therefore, the need to review the works analyzed so that the next ones editions can be reorganized in order to contemplate all the knowledge of the MTSK and, thus, develop material to support the training of quality teachers, which will contribute with meaningful teaching.